2018
DOI: 10.1007/s00520-018-4467-8
|View full text |Cite
|
Sign up to set email alerts
|

Social correlates of mental health in gastrointestinal cancer patients and their family caregivers: Exploring the role of loneliness

Abstract: Findings suggest that for advanced GI cancer patients and caregivers, emotional support from others alleviates feelings of loneliness, which may lead to better mental health. However, the benefits of emotional support appear to be primarily intrapersonal rather than interpersonal in nature. Additionally, participants endorsed low levels of social constraints, which might explain their lack of relation to loneliness and mental health. Continued examination of interdependence in social processes between cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Few studies assess the dyadic nature of social support perceived by the patient and caregiver on health‐related outcomes. A study of gastrointestinal cancer patients and caregivers found that one's emotional support alleviates loneliness, leading to better mental health outcomes; however, no interrelationships between patients' and caregivers' emotional support and outcomes were found . A study of caregivers and patients with advanced breast, colorectal, lung, or prostate cancer, found that one's social support was positively associated with their own exercise and diet and interrelationships varied over time; specifically, caregiver social support at baseline was associated with patient exercise and diet at 3 months, but patient social support at 3 months was only associated with caregiver diet at 6 months post intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies assess the dyadic nature of social support perceived by the patient and caregiver on health‐related outcomes. A study of gastrointestinal cancer patients and caregivers found that one's emotional support alleviates loneliness, leading to better mental health outcomes; however, no interrelationships between patients' and caregivers' emotional support and outcomes were found . A study of caregivers and patients with advanced breast, colorectal, lung, or prostate cancer, found that one's social support was positively associated with their own exercise and diet and interrelationships varied over time; specifically, caregiver social support at baseline was associated with patient exercise and diet at 3 months, but patient social support at 3 months was only associated with caregiver diet at 6 months post intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A study of gastrointestinal cancer patients and caregivers found that one's emotional support alleviates loneliness, leading to better mental health outcomes; however, no interrelationships between patients' and caregivers' emotional support and outcomes were found. 6 A study 7 of caregivers and patients with advanced breast, colorectal, lung, or prostate cancer, found that one's social support was positively associated with their own exercise and diet and interrelationships varied over time; specifically, caregiver social support at baseline was associated with patient exercise and diet at 3 months, but patient social support at 3 months was only associated with caregiver diet at 6 months post intervention. In a study 8 of distress and coping among cancer patients and caregivers, perceived social support was found to be positively associated with hope for their future while the interrelationship showed a negative association.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned facilitators and barriers for prognostic acceptance are well‐known resources or stressors in the context of malignant diseases like cancer 27–39 . Perhaps, patients were not able to clearly differentiate between factors affecting coping with the disease in general and factors impacting prognostic acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by the finding that loneliness is associated with poor mental health. 38 The feeling of causing problems and pain to loved ones, described as the phenomenon of a self-perceived burden to others, is associated with psychological distress in cancer patients. 39 These types of emotional suffering, tied to the social realm, may impede an accepting attitude toward the prognosis.…”
Section: Barriers For Prognostic Acceptancementioning
confidence: 99%
“…In the context of grave threats to their physical and mental health (Stefana, Youngstrom, Hopwood, & Dakanalis, 2020;Vigo et al, 2020), people living with cancer had to cope with several stressors including fear of SARS-CoV-2 infection, inadequate supplies, scarcity of information, nancial loss, stigma, and constrained freedom (Brooks et al, 2020). Thus, the psychological impact of mass quarantine in the context of a pandemic, in terms of stress, anxiety, depression, and poor sleep quality (Casagrande, Favieri, Tambelli, & Forte, 2020;, as well as isolation-related loneliness (Brooks et al, 2020;Hawryluck et al, 2004), could be even worse for cancer patients, who need emotional support from others to alleviate their feelings of loneliness and maintain mental health (Adams et al, 2016;Secinti et al, 2019). Although the restrictive measures have been essential to reduce the outbreak of the virus, they may have severe psychosocial consequences in people living with cancer.…”
Section: Introductionmentioning
confidence: 99%